ANALISIS HUJAN MAKSIMUM PADA DAERAH ALIRAN SUNGAI BABAK KABUPATEN LOMBOK BARAT - MUHAMAD YAMIN; BAGUS WIDHI DHARMA S. (GANEC SWARA, 2024)
Hydrological analysis is the most important measurement in determining runoff in order to find ways to overcome flooding. The flow rate that is the basis for calculating flood control and protection is the planned flood flow rate obtained from the sum of the volume of rain runoff and the flow rate of the water catchment area in question during a certain return period. This research is a case study using rainfall data for 10 years, namely 2014-2023. Rainfall prediction is an estimate of the amount of rain that will fall in a river basin. There are several methods for determining annual rainfall, the Gumbel distribution method, Pearson log type III, and the normal method. After analyzing the annual rainfall data obtained at the West Lombok Regency Meteorology, Climatology and Geophysics Agency office, using three methods, namely the EJ Gumbel method, the Log Person Type III method and the Normal method, where from the three methods the maximum rainfall difference was quite large, In the following table you can see the difference in the amount of maximum rainfall in the return period T years.